The role of digital technology in building social awareness and collective action among the younger generation - Nopindra, Alpari (Pt. Anagata Sembagi Education, 2025)
This study aims to analyze the role of digital technology in building social awareness and encouraging collective action among the younger generation. The main focus of the study is to identify how social media and digital platforms shape critical attitudes and empathy, and to explore various forms of social participation mediated by digital technology. The method used is the Systematic Literature Review (SLR), by collecting and analyzing various related literature from relevant journals, books, and articles to obtain a comprehensive picture of the phenomenon. The results of the study show that digital technology plays a significant role as a source of information and an effective mobilization tool, facilitating digital campaigns, online petitions, and fundraising that strengthen social solidarity. However, the study also reveals various challenges such as the spread of disinformation, the effects of algorithms, and the phenomenon of slacktivism that can hinder the effectiveness of technology in social change. An important implication of this study is the need to improve digital literacy and develop inclusive digital platforms as a strategy to empower the younger generation in fighting for social issues responsibly and sustainably